LEGAL ANALYSIS OF BANKRUPTCY IN THE PERSPECTIVE OF LEGAL PURPOSES - Theresia Anita Christiani (Jurnal Pembaharuan Hukum, 2021)
Law  Number  37 Of 2004 On Bankruptcy And Suspension Of Obligation For Payment Of Debts was formed to protect creditors and debtors. The purpose of Law is to realize the value of the benefit, justice, and legal certainty. This juridical fact shows that there are legal issues that deserve to be studied normatively. Based on the above background, the problem in this research is the right proposal concept. The application of articles 2 (1) and Article 8 (4) Bankruptcy And Suspension Of Debt Payment Obligations Law can achieve legal objectives. The results showed that the proposed concept to amend the Bankruptcy And Suspension Of Debt Payment Obligations Law took time. Concrete conceptual proposals so that the application of articles a (1) and Article 8 (4) can realize values by changing the attitude of judges who decide not only based on legal certainty. The Judge's attitude in deciding must also be based on the potential impact of Bankruptcy on the Debtor, whether it will lead to benefit or justice. The constitutive nature of decisions also affects changes in judge attitudes.